THE INFLUENCE OF LIFESTYLE AND FINANCIAL LITERACY ON THE CONSUMPTIVE BEHAVIOR OF BANDAR LAMPUNG UNIVERSITY MANAGEMENT STUDENTS CLASS OF 2021-2022 - Tantri Oktarini; Habiburahman (ZILLZELL MEDIA PRIMA, 2024)
The purpose of this study is to understand whether the impact of lifestyle and financial literacy affects the consumptive behavior of management students of Bandar Lampung University batch 2021-2022. The Quantitative Method is the method used in this study, with 356 students being the population and 177 students being selected to be sampled using the proportionate stratified random sampling method. The distribution of online questionnaires using Google Forms is the data collected, and multiple linear regression techniques are the techniques of this study. The results of the study stated that if consumptive behavior is influenced by the lifestyle of management students of Bandar Lampung University class of 2021-2022, consumptive behavior is not influenced by the financial literacy of management students of Bandar Lampung University batch 2021-2022. And consumptive behavior is simultaneously influenced by lifestyle and financial literacy.